2009
DOI: 10.1016/j.dnarep.2008.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Population-specific variation in haplotype composition and heterozygosity at the POLB locus

Abstract: DNA polymerase beta plays a central role in base excision repair (BER), which removes large numbers of endogenous DNA lesions from each cell on a daily basis. Little is currently known about germline polymorphisms within the POLB locus, making it difficult to study the association of variants at this locus with human diseases such as cancer. Yet, approximately thirty percent of human tumor types show variants of DNA polymerase beta. We have assessed the global frequency distributions of coding and common non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
(24 reference statements)
0
23
0
Order By: Relevance
“…These results indicate that identified variants are likely tumor-specific. None of the coding region mutations identified in this study are known to be germ line single nucleotide polymorphisms and are therefore likely somatic mutations that are associated with the tumor (43). Polymorphisms present in the UTR regions were also not observed in our samples (dbSNP, www.ncbi.nlm.nih.gov).…”
Section: Forty Percent Of Human Colorectal Tumors Harbor Mutations Inmentioning
confidence: 84%
“…These results indicate that identified variants are likely tumor-specific. None of the coding region mutations identified in this study are known to be germ line single nucleotide polymorphisms and are therefore likely somatic mutations that are associated with the tumor (43). Polymorphisms present in the UTR regions were also not observed in our samples (dbSNP, www.ncbi.nlm.nih.gov).…”
Section: Forty Percent Of Human Colorectal Tumors Harbor Mutations Inmentioning
confidence: 84%
“…Our typing methods are described in detail elsewhere. [5][6][7][8][9][10][11] As noted in those studies, an occasional typing failure persists after two attempts to obtain an acceptable result. Experience has shown that the yield from additional attempts at typing is extremely low.…”
Section: Methodsmentioning
confidence: 93%
“…This resource is well documented among genetic studies and details can be found there. 22,[31][32][33] All subjects gave informed consent under protocols approved by the committees governing human subjects research relevant to each of the population samples. Sample descriptions and sample sizes can be found in the Allele Frequency Database by searching for the population names…”
Section: Methodsmentioning
confidence: 99%